Characterization of the novel GlyT1 PET tracer [18F]MK‐6577 in humans. Issue 1 (24th September 2014) - Joshi, Aniket D.; Sanabria‐Bohórquez, Sandra M.; Bormans, Guy; Koole, Michel; De Hoon, Jan; Van Hecken, Anne; Depre, Marleen; De Lepeleire, Inge; Van Laere, Koen; Sur, Cyrille; Hamill, Terence G.
ABSTRACT Decreased glutamatergic neurotransmission is hypothesized to be involved in the pathophysiology of schizophrenia. Inhibition of glycine transporter Type‐1 (GlyT1) reuptake is expected to increase the glutamatergic neurotransmission and may serve as treatment for cognitive and negative symptoms of schizophrenia. In this article, we present human data from a novel GlyT1 PET tracer, [18F]MK‐6577. In the process of developing a GlyT1 inhibitor therapeutic, a PET tracer can assist in determining the dose with a high probability of sufficiently testing the mechanism of action. This article reports the human PET studies with [18F]MK‐6577 for measuring GlyT1 receptor availability at baseline in normal human subjects and occupancy with a GlyT1 inhibitor, MK‐2637. Studies were also performed to measure radiation burden and the baseline test‐retest (T‐RT) variability of the tracer. The effective dose from sequential whole‐body dosimetry scans in three male subjects was estimated to be 24.5 ± 2.9 µSV/MBq (mean ± SD). The time–activity curves from T‐RT scans modeled satisfactorily using a two tissue compartmental model. The tracer uptake was highest in the pons (VT = 6.7 ± 0.9, BPND = 4.1 ± 0.43) and lowest in the cortex (VT = 2.1 ± 0.5, BPND = 0.60 ± 0.23). VT T‐RT variability measured in three subjects was <12% on average. The occupancy scans performed in a cohort of 15 subjects indicated absence of a reference region. The in vivo potency (Occ50) of MK‐2637 was determined using two methods: A: Lassen plot with a population input function (Occ50 = 106 nM, SE = 20 nM) and B: pseudo reference tissue model using cortex as the pseudo reference region (Occ50 = 141 nM, SE = 21 nM). Synapse 69:33–40, 2015. © 2014 Wiley Periodicals, Inc.